2005
DOI: 10.1007/978-3-540-30578-1_11
|View full text |Cite
|
Sign up to set email alerts
|

An Agent Construction Model for Ubiquitous Computing Devices

Abstract: One of the main challenges for the successful application of agentbased systems in mobile and embedded devices is enabling application developers to reconcile the needs of the user to the capabilities and limitations of agents in the context of environments with changing and often limited resources. In this paper we present an attempt to move towards a solution through a framework for defining and reasoning about agents in a manner that is modular and reconfigurable at run-time. Departing from the theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Although the consequences of this are still to be completely understood, and although more work is needed, both analytical and experimental (or developmental), initial tests on PCs and high-end PDAs indicate that the difference is not significant. Through this example, and through others reported elsewhere (Ashri et al, 2003;Ashri and Luck, 2004) we have shown how the combination of SMART and actSMART can be used to support the development process of agent systems by offering three distinct but complementary views. Descriptive specification provides an abstract (and typically formal) means for systems specification, but largely ignores issues of system development.…”
Section: Discussionmentioning
confidence: 88%
“…Although the consequences of this are still to be completely understood, and although more work is needed, both analytical and experimental (or developmental), initial tests on PCs and high-end PDAs indicate that the difference is not significant. Through this example, and through others reported elsewhere (Ashri et al, 2003;Ashri and Luck, 2004) we have shown how the combination of SMART and actSMART can be used to support the development process of agent systems by offering three distinct but complementary views. Descriptive specification provides an abstract (and typically formal) means for systems specification, but largely ignores issues of system development.…”
Section: Discussionmentioning
confidence: 88%